Report of two cases of adenoid cystic carcinoma of Bartholin's gland and review of literature - Shih-Tien Hsu; Ren-Ching Wang; Chien-Hsing Lu; Yu-Min Ke; Yi-Ting Chen; Min-Min Chou; Esther Shih-Cho Ho (Elsevier, 2013)
Objective: Primary adenoid cystic carcinoma (ACC) of Bartholin's gland is a rare gynecologic malignancy. We report two cases from primary treatment to recurrence and the adjuvant treatment. Case Report: A woman aged 37 years presented with a mass on the right posterior labia minor and underwent right radical hemi-vulvectomy and right-side inguino-femoral node dissection. Final pathology showed ACC arising from Bartholin's gland with positive margins. She received adjuvant external beam radiation to the pelvis, right vulva, and groin area. However, distal metastasis occurred 42 months after initial treatment and she eventually died of multiple metastases. Another woman aged 48 years presented with a mass on the right posterior labia with intermittent pain. She underwent right hemi-vulvectomy and right inguino-femoral lymph node dissection only because pathology showed ACC of Bartholin's gland with negative surgical margins. Lung metastasis occurred 59 months after initial treatment. She took tamoxifen only and achieved stable disease status for 4 years. Conclusion: To date, about 70 cases have been reported. We treated our second patient with antiestrogen therapy for 4 years and achieved good quality of life and stable disease status. However, further study on hormone therapy for ACC of Bartholin's gland is needed.